ANALYSIS OF HEALTH LEVEL FINANCIAL STATEMENTS AT BPRS BHAKTI SUMEKAR USING CAMEL METHOD 2016-2020 - Putri Nur Vitasari; Abd Hadi; Basith Junaidy; Imroatul Azizah; Akhmad Yunan Atho’illah (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2018)
Abstract This research was conducted in order to determine the level of health at BPRS Bhakti Sumekar where the CAMEL method, that is Capital (capital), Asset Quality (asset quality), Management (management), Earning (profitability), and Liquidity (liquidity), was used in this study, and the period used was 2016-2020. Assessment of the bank's soundness level is also very important for a company itself, because by knowing the bank's health, the manager can make changes that can support the goodness and also the company's policies going forward. This research data collection method is by reviewing company records or documents. The results of the 2016 - 2020 BPRS Bhakti Sumekar Health Study show that the CAR ratio, BOPO is considered very healthy, while the PDN ratio is considered healthy even though the table does not show any movement in the level of health because BPRS Bhakti Sumekar is a non-foreign exchange bank, then FDR and ROA is considered healthy, and the ROE and FDR ratios are considered quite healthy because of all the results of these ratios, some are included in the moderate category; healthy